Assessing the efficacy of utilizing biochar derived from oil palm biomass as a planting medium for promoting the growth and development of oil palm seedlings - Tugiman, Erwan Syah; Mohd Yusoff, Mohd Zulkhairi; Hassan, Mohd Ali; Abd Samad, Mohd Yusoff; Ahmad Farid, Mohammed Abdillah; Yoshihito, Shirai (Elsevier, 2024)
The recent adoption of biochar in Malaysia's oil palm industry offers numerous benefits, including soil enhancement, resource efficiency improvement, pollution remediation, and greenhouse gas mitigation. With approximately 66.15% of agricultural land dedicated to oil palm cultivation, a substantial amount of biomass, mainly from empty fruit bunch (EFB) and mesocarp fibre (MF), is generated. This study focused on carbonizing MF and EFB at temperatures ranging from 580 to 695°C to produce biochar. The assessment of biochar's effectiveness as a planting medium in nurseries revealed significantly accelerated growth rates in seedlings cultivated in a composite of biochar and soil. At 8 months-after-treatment (MAT), the BMF-75 treatment showed remarkable growth enhancements, with the highest increase in height (64.9%), number of leaflets (60.5%), and girth size (55.3%) compared to the initial values at 3 MAT, indicating its effectiveness in promoting growth in oil palm seedlings. Additionally, compared to the control group, the biochar-mixed media resulted in favourable outcomes regarding the assimilation of both macro- and micro-nutrients. For instance, nitrogen uptake increased by 2.7% with BMF-50, magnesium by 25.2%, phosphorus by 24.1% with BEFB-75, calcium by 36.8% with BMF-75, chlorine by 10.5% with BMF-50, iron by 25.5% with BEFB-25, copper by 20.1% with BMF-25, and zinc by 6.3% with BMF-25. Additionally, biochar-treated soil exhibited higher organic carbon content, improved cation exchange capacity (CEC), enhanced nitrogen retention with greater biochar proportions, and likely improved soil fertility due to biochar’s porous structure. Further potential research can be explored to investigate its long-term effects on oil palm plantation.